The chemistry and pharmacology of putative synthetic cannabinoid receptor agonist (SCRA) new psychoactive substances (NPS) 5F‐PY‐PICA, 5F‐PY‐PINACA, and their analogs. Issue 7 (8th May 2019) - Banister, Samuel D.; Kevin, Richard C.; Martin, Lewis; Adams, Axel; Macdonald, Christa; Manning, Jamie J.; Boyd, Rochelle; Cunningham, Michael; Stevens, Marc Y.; McGregor, Iain S.; Glass, Michelle; Connor, Mark; et al.
Abstract: 5F‐PY‐PICA and 5F‐PY‐PINACA are pyrrolidinyl 1‐(5‐fluoropentyl)ind (az)ole‐3‐carboxamides identified in 2015 as putative synthetic cannabinoid receptor agonist (SCRA) new psychoactive substances (NPS). 5F‐PY‐PICA, 5F‐PY‐PINACA, and analogs featuring variation of the 1‐alkyl substituent or contraction, expansion, or scission of the pyrrolidine ring were synthesized and characterized by nuclear magnetic resonance (NMR) spectroscopy and liquid chromatography–quadrupole time‐of‐flight–mass spectrometry (LC–QTOF–MS). In competitive binding experiments against HEK293 cells expressing human cannabinoid receptor type 1 (hCB1 ) or type 2 (hCB2 ), all analogs showed minimal affinity for CB1 (p K i < 5), although several demonstrated moderate CB2 binding (p K i 5.45–6.99). In fluorescence‐based membrane potential assays using AtT20‐hCB1 or ‐hCB2 cells, none of the compounds (at 10 μM) produced an effect >50% of the classical cannabinoid agonist CP55, 940 (at 1 μM) at hCB1, although several showed slightly higher relative efficacy at hCB2 . Expansion of the pyrrolidine ring of 5F‐PY‐PICA to an azepane (8 ) conferred the greatest hCB2 affinity (p K i 6.99) and activity (pEC50 7.54, Emax 72%) within the series. Unlike other SCRA NPS evaluated in vivo using radio biotelemetry, 5F‐PY‐PICA and 5F‐PY‐PINACA did not produce cannabimimetic effects (hypothermia, bradycardia) in mice at doses up to 10 mg/kg. Abstract : 5F‐PY‐PICA, 5F‐PY‐PINACA, and analogs were synthesized and characterized. In competitive binding experiments and fluorescence‐based plate reader membrane potential assays, all ligands showed minimal affinity for CB1 (p K i < 5), although several demonstrated moderate CB2 binding (p K i = 5.45–6.99). 5F‐PY‐PICA and 5F‐PY‐PINACA did not produce cannabimimetic effects in mice at 10 mg/kg.